Nightmare distress mediated the correlation between autobiographical memory specificity and depression - Jiaxi Wang; Haote Fu; Xiaoling Feng; Heyong Shen (PLoS ONE, 2025)
In this study, we explored whether nightmare distress mediated the correlation between autobiographical memory specificity and depression. 112 participants provided their most recent dreams that happened within one month, and finished some scales that measured depression, autobiographical memory specificity, and nightmare distress. In line with our hypothesis, nightmare distress was the mediator that played a role in the relationship between autobiographical memory specificity and depression. In addition, we found that both nightmare distress and autobiographical memory specificity were correlated with the impact of a dream on one’s life story. By contrast, contrary to our hypothesis, we did not find any correlation between autobiographical memory specificity, or nightmare distress, and dream bizarreness. Potential implications from these results were discussed.